2015
DOI: 10.1007/s11205-015-0882-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adolescents’ Perceived Parental Involvement, Self-Efficacy Beliefs, and Subjective Well-Being: A Multiple Mediator Model

Abstract: The aim of this study was to examine the mediation roles of academic selfefficacy, social self-efficacy, and emotional self-efficacy on the relationships between parental involvement (i.e., paternal involvement and maternal involvement) and subjective well-being (i.e., positive affect, negative affect, and life satisfaction) in Malaysian adolescents. Participants were 802 Malaysian high school students from 14 public schools, with an age range of 15-17 years. Results of a multiple mediator model indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 143 publications
2
39
0
4
Order By: Relevance
“…This notion has been also supported by Caprara, Steca, Gerbino, Pacielloi and Vecchio (2006) who stated that perceived selfefficacy foster positive expectations about the future, to retain a high self-concept, to perceive life satisfaction and to experience more positive emotions. Other researchers have confirmed that adolescents' self-efficacy beliefs have positive effects on psychological well-being (Moeini et al, 2008;Tommasi et al, 2018), subjective well-being (Ma, Zeng & Ye, 2015;Yap & Baharudin, 2016) and quality of life (Taş, Öztürk-Çopur, Ünlü, Tüzün, & Özcebe, 2017). Telef and Ergün (2013) found, on sample composed by 311 Turkish adolescents, that academic, social, and emotional self-efficacy beliefs predicted their subjective well-being.…”
Section: Self-efficacymentioning
confidence: 89%
“…This notion has been also supported by Caprara, Steca, Gerbino, Pacielloi and Vecchio (2006) who stated that perceived selfefficacy foster positive expectations about the future, to retain a high self-concept, to perceive life satisfaction and to experience more positive emotions. Other researchers have confirmed that adolescents' self-efficacy beliefs have positive effects on psychological well-being (Moeini et al, 2008;Tommasi et al, 2018), subjective well-being (Ma, Zeng & Ye, 2015;Yap & Baharudin, 2016) and quality of life (Taş, Öztürk-Çopur, Ünlü, Tüzün, & Özcebe, 2017). Telef and Ergün (2013) found, on sample composed by 311 Turkish adolescents, that academic, social, and emotional self-efficacy beliefs predicted their subjective well-being.…”
Section: Self-efficacymentioning
confidence: 89%
“…Alunos com currículo escolar acrescido de atividades de esporte e artes estiveram mais satisfeitos com suas vidas (Orkibi, Ronen, & Assoulin, 2014). O apoio social dos professores e pares (e.g., Tian, Zhao, & Huebner, 2015) e o envolvimento dos pais (Yap & Baharudin, 2015) tiveram efeitos benéfi cos sobre a autoefi cácia dos adolescentes e estas, por sua vez, facilitaram experiências de BES. Além disso, as forças de caráter temperança e transcendência (Shoshani & Slone, 2013), propósito de vida e objetivos direcionados (Erylmaz, 2012) foram indicadores de BES na escola.…”
Section: Análise Qualitativa Dos Estudos Incluídosunclassified
“…With regard to data collection instruments in general, the use of scales and questionnaires predominated, as shown in Table 3. To evaluate self-effi cacy, 17 different instruments were adopted, with the most used being: measures containing subscales evaluating academic selfeffi cacy: Self-effi cacy Scales (Perceived Competence Scale for Children-PCSC; Chung & Elias, 1996), Escala de Autoefi cácia Acadêmica (Guerreiro-Casanova et al, 2011), Cuestionario sobre la Autoefi cacia Académica General (Gaxiola & Armenta, 2016) and Self-effi cacy Questionnaire for Children (Yap & Baharudin, 2016). These were followed by, the Self-Effi cacy Scale for Occupational Activities (EAAOc; Noronha & Ambiel, 2008;Nunes & Noronha, 2009; and the evaluation of self-effi cacy for career development: Career Decision-making Self-effi cacy Scale-Short Form (CDMSES-SF; Gushue, 2006), Career Decision Self-effi cacy Scale-Short Form (CDSE; Di Fabio & Kenny, 2015), and Inventário de Autoefi cácia em Desenvolvimento da Carreira (CD-SEI; Leal et al, 2015).…”
Section: Type(s) Of Evaluation Of the Self-effi Cacy And Social Domainsmentioning
confidence: 99%
“…Regarding the social domain of investigation shown in Table 3, 53% of the studies involved only the school domain (n=10), as in the studies conducted by Chung and Elias (1996) and Yap and Baharudin (2016), for example. There were also four studies (Guerreiro-Casanova et al, 2011;Leal et al, 2015;Noronha & Ambiel, 2008;Ventura & Noronha, 2014) that jointly investigated the school and family domains, as well as three studies (Carvajal et al, 1999;Di Fabio & Kenny, 2015;Gonzalez et al, 2014) that analyzed the school domain and the peer group simultaneously.…”
Section: Type(s) Of Evaluation Of the Self-effi Cacy And Social Domainsmentioning
confidence: 99%